STUDI LITERATUR: ANALISIS KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR BURSA EFEK INDONESIA DITINJAU DARI PERSPEKTIF SIGNALING THEORY - Sudirman, Nengsi; Rifqiansyah, Rifqiansyah; Darmono, Darmono (Transpublika Publisher, 2024)
This article aims to analyze the financial performance of manufacturing companies listed on the Indonesian stock exchange from a signaling theory perspective. This research uses a descriptive-qualitative approach by looking at secondary data literature. The data sources obtained come from scientific publications, papers, and articles that summarize information relevant to the research topic. Sample selection is carried out by observing and analyzing various information related to the research to combine research findings that are the same as the researcher's topic. The research results explain that financial performance analysis can be used as information in decision-making. The signaling theory view indicates that companies will try to provide positive signals or information to investors through the company's annual report, in which financial information is presented.